2003
DOI: 10.1098/rspa.2002.1042
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological effects of the eclipse of 11 August 1999 in cloudy and clear conditions

Abstract: Sensitive high-resolution meteorological observations revealed dynamical atmospheric e¬ects despite the presence of cloud. Short-term eclipse-related changes dominated over temperature, wind speed and wind directions associated with the synoptic conditions, and 35 min period gravity waves were detected in surface-pressure observations. Theoretical calculations for solar radiation changes were compared with observations made during the 97% partial eclipse in clear skies at Reading, Berkshire, and used to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
154
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(173 citation statements)
references
References 20 publications
16
154
3
Order By: Relevance
“…Temperature, relative humidity, wind and cloudiness are among the most common meteorological parameters measured and observed in experimental campaigns during solar eclipses (e.g. Anderson, 1999;Fernandez et al, 1993Fernandez et al, , 1996Aplin and Harrison, 2002). Although the results of most meteorological studies provide similar patterns of temperature changes, the precise drop may differ depending on several factors (timing, synoptic situation, surrounding environment, percentage of sun occultation etc).…”
Section: Synoptic Meteorological Situationmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature, relative humidity, wind and cloudiness are among the most common meteorological parameters measured and observed in experimental campaigns during solar eclipses (e.g. Anderson, 1999;Fernandez et al, 1993Fernandez et al, , 1996Aplin and Harrison, 2002). Although the results of most meteorological studies provide similar patterns of temperature changes, the precise drop may differ depending on several factors (timing, synoptic situation, surrounding environment, percentage of sun occultation etc).…”
Section: Synoptic Meteorological Situationmentioning
confidence: 99%
“…An "eclipse wind" has been also reported during many eclipses (e.g. Aplin and Harrison, 2002), although in some cases it could be also related to subjective perception of a pronounced wind chill effect (Anderson, 1999). According to recent observations (e.g.…”
Section: Synoptic Meteorological Situationmentioning
confidence: 99%
“…Wind direction changes have variously been attributed to dynamic effects associated with cooling in the umbra and penumbra (e.g. [11]), the development of local drainage flows [12,[19][20][21] or suppression of sea breeze circulations (e.g. [23]).…”
Section: (G) Topographymentioning
confidence: 99%
“…[2,5,7,9,11,12,15,19,25]) and are usually attributed to the increase in near-surface stability which reduces turbulent mixing, sometimes allowing near-surface flow to decouple from the geostrophic flow. Segal et al [15] showed that NSAT decreases were more rapid following the decoupling of winds at low levels.…”
Section: (G) Topographymentioning
confidence: 99%
See 1 more Smart Citation